(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Religiosity as a scientific trend is still forming, that is why the science itself has not defined and specified the problematic field of research. The study of religious culture, the definition of moral universalities’ and nations – specific ethnoses presentations and norms’ correlation features of interpretation in them of common to all mankindmoral demands are very actual. Interreligious harmony is the most important element of stability in any civil society. Saving interfaith and international peace can be built only on the joint relationship between the state and religious associations. Additionally, for the modern Kazakhstan it is characterized that the coexistence on equal rights of different religions, balance the relationship between which is supported by the development of the same interest of state policy to all confessions, formation a culture of tolerance in terms of parity before the law. Special importance is the reinterpretation of dialectical relationship of religious aspects in the Kazakh culture, their appearance in the mentality, lifestyle, social memory and the process of self-identification. In this article are available the materials about problems of interethnic and interfaith relations in Kazakhstan. The paper used research methods such as the unity of the methods of historical and logical, concrete historical approach, comparative method and system analysis. Key words: secular, civilsociety, social psychology, multicultural, tolerance, dialogue, religiousculture, humanism.